PENGARUH LATIHAN SMALL SIDED GAMES TERHADAP TEKNIK DASAR PERMAINAN SEPAKBOLA - Waliyandi, Waliyandi; Atiq, Ahmad; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem discussed in this study is the low and inaccurate basic technical skills of football games in extracurricular activities at SMAN 4 Singkawang. The purpose of this study was to detremine the effect of small sided games training on the basic trchniques of soccer games in extracurricular activities at SMAN 4 Singkawang. The experimental research method involves two variables namely the independent variable small sided games exercise and the dependent variable, which is the basic technique of soccer games. The population of soccer extracurricular students at SMAN 4 Singkawang is 25 students, the sampling is using the total sampling method, the researchers take all of the population, with a total sample of 25 students. This research technique uses tests and measurements, namely football basic technical tests. Data analysis using t-test formula. The result of this study indicate that there is an effefct of the Small Sided Games training on the basic techniques of playing football in extracurricular activities at SMAN 4 Singkawang. This can be proven based on the calculation results, where the value of the ttest is 4.75 > the value of ttable (1,711), so that the alternative hypothesis (Ha) is accepted and the hypothesis (Ho) is rejected. This means that there is an influence of the Sall Sided Games training on the basic techniques of playing football in extracurricular activities at SMAN 4 Singkawang.Keywords: Small Sided Games, Basic Soccer Techniques, Soccer Extracurriculars